Improved testing method of dynamic cone penetrometer in laboratory for evaluating compaction properties of soil subgrade. Issue 2 (2nd April 2016) - Yang, Bo; Zhang, Rui; Zha, Xudong; Liu, Chuang; Pan, Qinxue
Abstract : Based on the wide application of dynamic cone penetrometer (DCP) in detecting engineering for subgrade, this paper analyses the influence of moisture content on penetration ratios (PRs) when DCP penetrates the compaction specimens of soil and proposes a laboratory testing method of DCP. Through contrasting experiments in the laboratory, degree of compaction, initial moisture content and PRs are regressed with multivariate linear correlation equations of which the correlation coefficients are all greater than 0.9. The corresponding tests including the DCP test, portable falling weight deflectometer test, CBR test and sand cone test are also carried out in the field, the field test results were regressed according to the corresponding regression equations proposed in the laboratory. Parameters of the regression equations for laboratory and field test results are compared and deviations are analysed, the results show that the relative deviations are less than 0.1, which indicates that there are good consistencies between laboratory and field regression equations. Therefore, as long as the moisture content and PR of the soil are measured, compaction qualities and mechanical indexes of subgrade in the field can be accurately predicted according to multivariate regression proposed in the laboratory.